2014
DOI: 10.3168/jds.2014-8067
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of pregnancy viability in bovine in vitro-produced embryos and recipient plasma with Fourier transform infrared spectroscopy

Abstract: We analyzed embryo culture medium (CM) and recipient blood plasma using Fourier transform infrared (FTIR) metabolomics to predict pregnancy outcome. Individually cultured, in vitro-produced (IVP) blastocysts were transferred to recipients as fresh and vitrified-warmed. Spent CM and plasma samples were evaluated using FTIR. The discrimination capability of the classifiers was assessed for accuracy, sensitivity (pregnancy), specificity (nonpregnancy), and area under the receiver operator characteristic curve (AU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 47 publications
3
38
0
Order By: Relevance
“…In a recent study, IVF and ICSI derived cattle embryos were associated with spent culture media with a different metabolomic signature (Li et al 2018). Dual assessment of the systemic metabolome of recipient cows, together with the metabolome of spent culture media, could predict the pregnancy outcome for transferred IVF embryos (Munoz et al 2014a) and conventional superovulated embryos (Munoz et al 2014c). Notwithstanding recent progress with application of metabolomics in IVF, limitations have been identified and the field remains at an early stage (Cuperlovic-Culf et al 2010;McRae et al 2013;Uyar and Seli 2014;Munoz et al 2014c;Krisher et al 2015;Rodgaard et al 2015).…”
Section: Assisted Reproductionmentioning
confidence: 99%
“…In a recent study, IVF and ICSI derived cattle embryos were associated with spent culture media with a different metabolomic signature (Li et al 2018). Dual assessment of the systemic metabolome of recipient cows, together with the metabolome of spent culture media, could predict the pregnancy outcome for transferred IVF embryos (Munoz et al 2014a) and conventional superovulated embryos (Munoz et al 2014c). Notwithstanding recent progress with application of metabolomics in IVF, limitations have been identified and the field remains at an early stage (Cuperlovic-Culf et al 2010;McRae et al 2013;Uyar and Seli 2014;Munoz et al 2014c;Krisher et al 2015;Rodgaard et al 2015).…”
Section: Assisted Reproductionmentioning
confidence: 99%
“…These applications have already been well revised [13]. One FTIR study [14] reports the sensitivity and specificity of 76.8% and 65.7%, respectively, for 24-hour embryo culture media. Another study with NMR [15] found embryo viability with the specificity and sensitivity of 88.2% and 88.2%, respectively.…”
Section: Introductionmentioning
confidence: 98%
“…The presence of cytokines and growth factors in follicular fluid is crucial for determining oocyte quality (reviewed by Dumesic et al, 2015). In this context, the metabolic characterization of the culture media, in which IVP embryos are kept for many hours, may represent an important non-invasive tool to either indicate possible predictive biomarkers of viability or to explain IVP outcome afterwards (Muñoz et al, 2014). …”
Section: Introductionmentioning
confidence: 99%